The effect of recycled thermoplastic elastomer(TPE) mixing ratio on the tensile strength of thermoplastic elastomer (TPE) polymer - Muhamad Ifrad, Ibrahim (2013)
Recycling polymer has become an important field in a polymer research especially in recent years. This is because, by recycling the polymer, we can prevent pollution from happen. In this research, thermoplastic elastomer (TPE) is used, TPE is a class of copolymers or a physical mix of polymers usually a plastic and a rubber which consist of materials with both thermoplastic and elastomeric properties. The dog-bone shape mould with standard size ASTM D638 designed by using AutoCAD software and fabricated by using electrical discharge machining machine and milling machine to be used as a specimen. The virgin TPE come from raw material of TPE in the resin form whereas the recycled TPE come from injection moulded virgin dog-bone shape specimens that have been crushed by using crusher machine. After that, recycled TPE and virgin TPE are then mixed according to the desired mixing ratio and injection moulded by using injection moulding machine. Then, the specimens undergo tensile strength test by using universal testing machine in order to determine which mixing ratio produce highest tensile strength. As a result, the mixing ratio that produce highest tensile strength is 100% virgin TPE and the second highest is 100% recycled TPE. This is due to the ability of material mix together and produces strong bonding within each other.